The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.omtn.2018.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Recognition and In-Vitro-Targeted Inhibition of Renal Cell Carcinoma Using a DNA Aptamer

Abstract: Renal cell carcinoma (RCC) is the most common malignant tumor of the urinary system, and it has a high frequency of local invasion and distant metastasis. Although multiple advances have been made in the diagnosis and therapy of RCC, the vast majority of patients with metastatic RCC remain incurable. In this study, an aptamer named SW-4 against RCC 786-O cells was identified from a known sequence pool. The identified aptamer exhibited high binding affinity for target cells with dissociation constants in the na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 23 publications
1
33
0
Order By: Relevance
“…Notably, pathway enrichment analysis revealed that MTFR2 co-expressed genes were significantly enriched in the cell cycle. Cell proliferation depends on an orderly cell cycle process [55]. The results of our plate cloning assay confirm that MTFR2 can promote cell proliferation.…”
Section: Discussionsupporting
confidence: 70%
“…Notably, pathway enrichment analysis revealed that MTFR2 co-expressed genes were significantly enriched in the cell cycle. Cell proliferation depends on an orderly cell cycle process [55]. The results of our plate cloning assay confirm that MTFR2 can promote cell proliferation.…”
Section: Discussionsupporting
confidence: 70%
“…In the past few decades, many specific aptamers have been developed for tumor treatment ( Table 2 ), such as breast cancer ( Liu et al, 2017 ), colorectal adenocarcinoma ( Chen et al, 2017 ), lung cancer (2018), liver cancer ( Zhang G.Q. et al, 2019 ), prostate cancer ( Gray et al, 2018 ), leukemia ( Tan et al, 2019 ), renal cell carcinoma ( Zhang et al, 2018 ), oral cancer ( Simmons et al, 2014 ), cervical cancer ( Carvalho et al, 2019 ), bladder cancer ( Yao et al, 2020 ), stomach cancer ( Ding et al, 2015 ) and multiple myeloma ( Waldschmidt et al, 2017 ).…”
Section: Screening and Development Of Therapeutic Aptamers Against Cancer Cellsmentioning
confidence: 99%
“…Using a mouse model of DN, aptamer treatment significantly attenuated the pathologic phenotype [ 56 ]. Aptamers have also been developed with high binding affinity and specificity to RCC cell lines [ 58 , 97 ], with the potential for their use in the identification and targeting of RCC. Zhang et al [ 58 ] identified an aptamer (SW-4) with selective binding to the RCC 786-O cell line that inhibited cell proliferation by cell cycle arrest.…”
Section: Oligonucleotides Used In Therapeuticsmentioning
confidence: 99%
“…Aptamers have also been developed with high binding affinity and specificity to RCC cell lines [ 58 , 97 ], with the potential for their use in the identification and targeting of RCC. Zhang et al [ 58 ] identified an aptamer (SW-4) with selective binding to the RCC 786-O cell line that inhibited cell proliferation by cell cycle arrest. Furthermore, the authors demonstrated that SW-4 retained targeting specificity to RCC in vivo following tail vein injection of the aptamer in a 786-O xenograft mouse model, and also maintained recognition of clinical RCC tissue samples.…”
Section: Oligonucleotides Used In Therapeuticsmentioning
confidence: 99%